Bioethics & politics of human embryonic stem cell science in the EU's 6th framework programme - Salter, Brian (Henry Stewart Talks, 2007)
Cultural politics and bioethics, Regulatory options in human ESC science, National differences, Ethical debates in the European Parliament, Conflict over the human embryo, Politicians versus experts, The Human Tissues Directive, Bioethicists as an emerging power group
Archived at 2021/02/25